The Syntactic Efforts to The Sheikh Mohammad Muhi Ad-Deen Abdulhameed in Ibin Akeel's Explanation (Journal of the College of Education for Women, 2019)
The Arabic language is one of the honoring languages that has a supreme status. Being the language of the Holly Qura'an has increased its refinedness and spread in the Islamic and non-Islamic world. It has become the means of communication and conversation, and the language of knowledge and thought. The multiplicity of its dialects and accents is a sign of its capacity. Many Roman, Persian, and Greek sciences and arts have been translated and Arabicized into it. It has further become the formal language of communication in the world. Many great Arab scholars have played a role in examining it to maintain and elevate it. One of these scholars is the great scientist Mohammad Muhi Ad-Deen Abdulhameed who has done great syntactic efforts in Ibin Akeel's explanation, the topic of the present research. This is because Mohammad has great efforts and status in laying the bases of Arabic syntax through his categories, invaluable publishing in different branches of Arabic language, such as: syntax, morphology, literature, rhetoric, especially in the explanation of Ibin Akeel. The paper will also shed light on Mohammad's origin, date of birth, age, bringing up, professors, his students, the important events that affected his academic life, his scientific and religious orientations, and the most important publishing that enriched the Arabic sciences. Then, the researcher will hopefully cover the most important issues that have been tackled by this respectful scientist in his publishing or in what others have written about him. The tackledissues either reflect his own ideas, or represent his efforts in following the previous scholars. In the human history, the number of great scholars, Imams, and scientists differs from age to age. One of these scholars is the great scientist Mohammad Muhi Ad-Deen Abdulhameed. The reason behind choosing this great figure is the desire to serve the Arabic language, and cover all what has been written on this figure and his publishing. Besides, it is hoped to give this great figure the due respect and importance as an appreciation to the things he provided to the Arabic language that in return helped elevate its status among the other world languages and enrich it with various lines of knowledge; especially when the amount of studies on this figure is still meager.